Boundary Value Problems for q-Dierence Equations and Inclusions with Nonlocal and Integral Boundary Conditions - Ahmad, Bashir; Ntouyas, Sotiris K. (Mathematical Modelling and Analysis, 2014)
In this paper, we study boundary value problems for q-difference equa-tions and inclusions with nonlocal and integral boundary conditions. Some new exis-tence and uniqueness results are obtained by using a variety of xed point theorems.Examples are given to illustrate the results.